A técnica do filme São Jerônimo, de Júlio Bressane, segundo um desenho do tempo - Magalhães, Iara Helena (2007)
This paper aims to study the compositional technique of cinema, researching the technique of creation of the movie São Jerônimo, by Júlio Bressane, based in the design of the time. São Jerônimo was constructed from a series of documents, readings, paintings, thesis that traverse between fascination for iconography linked to the saint and the immanence of the film construction. A process of translation of the process of translating. The focus of this research is the time. The time that arises from the emancipation of the movement through light and sound time in the cinematographic image and drama. This paper was based theoretically in two works by Gilles Deleuze The image-movement and The image-time. The study of the concept image-time time emancipated from movement as the original regime of imagine and sign of the modern cinema, made it possible for us to see, hear and feel the time in São Jerônimo. We also studied the Peircian semiotics, the principles of the filmic analysis, the role of the sound in the cinema, the theoretical production of Brazilian researchers on critique of movies and unpublished works about photography in the creation of films.The method used to do the reading of the film involved three stages: in the first we studied the qualities, the shapes, the codes and their materialization in the composition of the audio-visual images, observing the framing, decoupage, the movement of the camera, the montage and materialization of the rhythmical ideas and their interactions; in the second stage we investigated the audiovisual images as aesthetical objects through the image-time concept; in the third stage we analyised the disjunction between the visual and audio images of the movie.The analysis of São Jerônimo made us to come to the following conclusion: its images immobilized the visual and sound aspects. The sound tries to take the film out of the visual field framed in the screen, in a centrifugal movement, but it detains itself in several deviations, tending to the purity of sound, while the visual aspect rapidly drags us to territories of excess or shortage of light the desert and Rome in a centripetal movement that leads, however, to disconnected and decentralized places, resisting to the photo grams and the images in movement. São Jerônimo, design of a moving material that cuts the cinematographic plan and rearrange the cuts that present the time. Jerônimo, Bressane and Deleuze s intercessor